Structure-Activity Studies on the Hypertrehalosemic Hormone II of the Stick Insect Carausius morosus (Phasmatodea): Carbohydrate-Mobilization and Cardio-Stimulatory Activities - Katali, Ottilie K. H.; Marco, Heather G.; Gäde, Gerd (Frontiers in Physiology, 2020)
The corpora cardiaca of the Indian stick insect, Carausius morosus, synthesize two decapeptide neuropeptides of the adipokinetic hormone (AKH) family, both of which can increase the trehalose levels in the hemolymph when the stick insect is ligated between the head and the thorax. Here, we use two biological assays to assess the potencies of 19 AKH analogs in ligated C. morosus: the carbohydrate-mobilizing assay measures the change in the levels of circulating carbohydrates following injection of a substance, while the semi-exposed heart assay measures a change in heart beat rate after the peptide is applied onto the heart. With the endogenous AKH (Carmo-HrTH-II) as lead peptide, we report here on seven naturally-occurring AKH peptides (bioanalogs) selected for testing because of a single or double amino acid replacement, or for being octapeptides. Single amino acid substitutions by an alanine residue at all positions of Carmo-HrTH-II, as well as analogs modified at the termini were also investigated to give a comprehensive view of ligand-receptor interaction at the physiological level in a hemimetabolous insect that practices thanatosis (feigning death). Only small changes are elicited in the bioassays, but the results from the two tests are comparable bar one or two anomalies. Results show that analogs modified at the termini have no or reduced activity. Regarding structural requirements of a ligand, the C. morosus AKH receptor appears to be strict: octapeptides are not preferred and many of the decapeptide analogs failed to reach 50 % activity relative to Carmo-HrTH-II. The data implies that the HrTH receptor in C. morosus mostly does not tolerate shorter peptides and single amino acid replacements in most places of the native AKH peptide. This information is important if environmentally friendly insect-specific pesticides are made based on an insect AKH as lead peptide: stick insects that are normally not viewed as pest insects may not be easily targeted by cross-reactive AKH mimetics directed at harmful insects, due to the very specific amino acid requirements to activate the C. morosus AKH receptor.